Determinants of the Quality of Financial Statements With Accounting Information System as Intervening Variables - Lydianti Budiman, Tania; Apollo Daito (Dinasti Publisher, 2022)
The objective..of this study is to prove empirically the influence.of leadership, organizational.culture, and.human resource competence on the.quality of financial reports which was mediated by accounting information systems. This study applied purposive sampling method. Researchers conducted a survey towards 31 Regional Apparatus Organizations (OPD) in the Serang city and research sample involved the head of finance department and the treasurer. Data was collected through interviews and distributing questionnaires, thenxanalyzed using SEMxPLS with Smart PLS software versionx3.2.8. Thexresults.showed: (1) leadership, organizational culture, human resource competence, accounting information system had a positive and significant effect on the quality of financial reports, (2) leadership, organizational culture, human resource competence had a positive and significant effect on accounting information systems (3) the accounting information system was not able to mediate leadership with the quality of financial reports. (4) the accounting information system was able to mediate organizational culture with the quality of financial reports, (5) the accounting information system was not able to mediate the competence of human resources with the quality of financial reports.